2021
DOI: 10.1039/d1cp01106e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface contamination on the interfacial properties of CO2/water/calcite systems

Abstract: Understanding the wetting properties of reservoir rocks can be of great benefit for advanced applications such as the effective trapping and geological storage of CO2. Despite their importance, not all...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 65 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…It should be noted that the challenges mentioned in relation to the contact angle for IFT also exist and should be solved appropriately [134][135][136][137] .…”
Section: Sessile Dropmentioning
confidence: 99%
“…It should be noted that the challenges mentioned in relation to the contact angle for IFT also exist and should be solved appropriately [134][135][136][137] .…”
Section: Sessile Dropmentioning
confidence: 99%
“…The number of water molecules in various MD simulation work extends to a wide range, from several hundreds to over ten thousands. [1][2][3][4][5][6] Based on a comparison of the water contact angle on calcite with various water molecules, Silvestri et al found that the water contact angle on calcite became insensitive to the size of the droplet if the number of water molecules was more than 8700. 5 In studying the wettability of a rough graphite substrate, Yaghoubi and Foroutan suggested that the line tension effect was negligible when the number of water molecules was 3000.…”
mentioning
confidence: 99%